The Effect of Internal Auditing on Organizational Performance: A case study of Mukono District Local Government - Merek Wandera (Uganda Christian University, 2023)
The study examined the effect of internal audit on organizational performance in the public sector: a case study of Mukono district local government. It specifically focused on three objectives which included: to examine the effect of internal control systems on organizational performance of Mukono district local government, to examine the effect of audit risk management on organizational performance of Mukono district local government and to examine the effect of governance processes on organizational performance of Mukono district local government. The study adopted a cross - sectional research design, both qualitative and quantitative study approaches were used, sample size was 40 participants who were chosen using purposive and simple random sampling and were served close ended questionnaires while secondary data was accessed from organizational records. The study revealed that internal control systems in an organization greatly impact the quality of work done and improve generally the organization’s performance, audit risk management helps reduce the chances of risk occurrence in the audit processes and governance structures help set out clear guidelines that must be followed in executing work hence emphasizing specification and specialization. The study recommended that more emphasis should be put on internal auditing by training all employees on how to use IFMS, there is need to recruit more human resource with knowledge and expertise in the field of accounting, finance and auditing because some of those around had no clue and finally more measures should be put in place to enhance internal control systems.
This is a dissertation.